2013
DOI: 10.1177/1350650113498230
|View full text |Cite
|
Sign up to set email alerts
|

Micro-slippage effects in pre-rolling induced by a disturbed and undisturbed pendulum with spherical supports

Abstract: Dynamics of small free swings of a pendulum supported by two spherical balls pre-rolling on a flat basis are considered to investigate the occurrence of micro-slippage at the contact interface between the balls and the flat surface. The basic mechanisms of this micro-slippage are investigated, showing how geometric conditions could initiate and magnify microslippage rather than assuming that these effects are core characteristics in any rolling system. This article also discusses the energy dissipation of a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…[4][5][6][7] to the experimental studies of the parameters of contact interactions of elastic bodies with the aid of a pendulum tribometer. The results of these valuable studies have stimulated the emergence of the present paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] to the experimental studies of the parameters of contact interactions of elastic bodies with the aid of a pendulum tribometer. The results of these valuable studies have stimulated the emergence of the present paper.…”
Section: Discussionmentioning
confidence: 99%
“…In [4][5][6][7] it has been shown that a pendulum tribometer at small swinging amplitudes allows for determination of the physical parameters of the materials under study without destroying their surface. The main attention is paid to measuring the coefficient of rolling friction f r .…”
Section: Introductionmentioning
confidence: 99%
“…No slippage was noticed between materials at the interface of contact according to the recorded graphs due to the highly stable pendulum as discussed previously. This was possible with the appropriate design of the pendulum for pure rolling as it was mentioned previously [25,26].…”
Section: Pre-rolling Under Dry Conditions 41 Determination Of Pre-rol...mentioning
confidence: 98%
“…Ранее авторами данной работы был разработан двухконтактный маятниковый прибор, в котором физический маятник совершал свободные затухающие качания с амплитудой, существенно меньшей угла упругого контакта, опираясь двумя одинаковыми шариками на плоскую исследуемую поверхность. Центр масс маятника находился на пятне контактов шариков [23,24].…”
Section: маятниковые приборы для исследования сил адгезииunclassified